2019
DOI: 10.2147/ijn.s207098
|View full text |Cite
|
Sign up to set email alerts
|

<p>PEG-coated and Gd-loaded fluorescent silica nanoparticles for targeted prostate cancer magnetic resonance imaging and fluorescence imaging</p>

Abstract: Background: Multimodal imaging probes have become a powerful tool for improving detection sensitivity and accuracy, which are important in disease diagnosis and treatment. Methods: In this study, novel bifunctional magnetic resonance imaging (MRI)/fluorescence probes were prepared by loading gadodiamide into fluorescent silica nanoparticles (NPs) (Gd@Cy5.5@SiO 2 -PEG-Ab NPs) for targeting of prostate cancer (PCa). The physicochemical characteristics, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Dynamic light scattering (DLS) curves (Figure 1D) revealed that the average diameter of the NPs was 162.50 nm, suggesting that the DLS measured these NPs as slightly larger than the TEM, which might be the result of the rehydration of the NPs in the aqueous solution used for the DLS evaluation. As expected, the zeta potential of the MSN was negative (Figure 1E), whereas the moderate size of these particles should help avoid renal clearance and uptake to the reticuloendothelial system (RES) in the liver, which were both essential for increasing circulation time (Phillps et al, 2010;Koo et al, 2011;Shao et al, 2011;O'Connell et al, 2017;Jiang et al, 2019). The EDS (Figure 2B) spectrum confirmed that the red circle appearing in Figure 2A indicates Gd-existence with an atomic fraction of 0.91% (atom.%) Gd (Table 1).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Dynamic light scattering (DLS) curves (Figure 1D) revealed that the average diameter of the NPs was 162.50 nm, suggesting that the DLS measured these NPs as slightly larger than the TEM, which might be the result of the rehydration of the NPs in the aqueous solution used for the DLS evaluation. As expected, the zeta potential of the MSN was negative (Figure 1E), whereas the moderate size of these particles should help avoid renal clearance and uptake to the reticuloendothelial system (RES) in the liver, which were both essential for increasing circulation time (Phillps et al, 2010;Koo et al, 2011;Shao et al, 2011;O'Connell et al, 2017;Jiang et al, 2019). The EDS (Figure 2B) spectrum confirmed that the red circle appearing in Figure 2A indicates Gd-existence with an atomic fraction of 0.91% (atom.%) Gd (Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…These spectra also included a peak at 1,636 cm −1 , corresponding to the bending vibration of -OH. Taken together, these patterns were representative of the characteristic absorption peaks of MSN materials (Figure 5) (Ni et al, 2016;He et al, 2019;Jiang et al, 2019;Cai et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, to avoid the accumulation of proteins in the blood serum that lead to endocytosis and improve the circulation time of nanoparticles, PEG has been used. Gd@Cy5.5@SiO2 nanoparticles were prepared in conjugation with the antibody YPSMA-1 against prostate-specific membrane antigen (PSMA) to improve the target specificity of prostate cancer imaging material [120]. PSMA is a transmembrane protein of type II that is specifically present in prostate cancer cells with high uniformity and frequency and some other normal tissues.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Therefore, it is an ideal targeting agent for the imaging and treatment of prostate cancer. PEG-coated and Gd-loaded targeted fluorescent silica nanoparticles were synthesized by reverse microemulsion and carbodiimide method [120]. The biosafety and targeting ability of the nanoparticles was confirmed by in vivo and in vitro studies.…”
Section: Prostate Cancermentioning
confidence: 99%
“…60 Also, the cytotoxicity of PEG-coated and Gdloaded fluorescent silica NPs using LNCaP and PC3 Cells was studied by Jiang et al They found no significant cytotoxicity after 24 h of incubation with NPs, suggesting that these NPs exhibited no toxicity toward LNCaP and PC3 cells. 61 Nörenberg et al examined the potential gadolinium (Gd) accumulation in the brain of healthy mice after long-term oral administration of Gd-containing food pellets and investigated whether Gd could lead to adverse central nervous system (CNS) effects. They suggested that low levels of intracerebral Gd do not lead to detectable CNS effects, and in particular did not impair locomotor abilities in the healthy murine model, even over a very long exposure time.…”
mentioning
confidence: 99%